Суспільна небезпека та деякі правові позиції кваліфікації згвалтування - Андрусяк, Ганна Миколаївна; Andrusiak, H. (Східноєвропейський національний університет імені Лесі Українки, 2019)
Стаття присвячена проблемам кваліфікації зґвалтування як одного з найбільш тяжких злочинів проти особи у всьому світі, оскільки в багатьох випадках вони супроводжується вбивством. Суспільна небезпека статевих злочинів визначається насамперед посяганням на статеву свободу чи статеву недоторканість особи, а також заподіянням шкоди здоров’ю, честі і гідності особи, нормальному фізичному, психічному та соціальному розвитку дітей і підлітків. Зґвалтування часто супроводжується вбивством жертви ґвалтівником в момент зґвалтування, у процесі боротьби з потерпілою і подолання її спротиву, або безпосередньо після зґвалтування, щоб уникнути викриття, помститися за опір, з мотивів садизму тощо. Проаналізована та доведена позиція про допустимість заподіяння тяжкої шкоди ґвалтівнику.The article highlights the legal issues of qualifying the rape cases as the most severe crimes in the world against a person since, in a number of cases, rape is followed by murder. The social danger of sexual assaults lies primarily in the encroachment on sexual freedom or sexual inviolability of the person, bringing harm to the health, honor, and dignity of the person, physical, mental, and social development of children and adolescents. Rape is often accompanied by the murder of the victim by the rapist at the time of the rape, in the process of fighting to overcome the victim, or immediately after the rape to avoid reprimand, or as a revenge for the resistance, in some cases, for the reasons of sadism and the like. The study analyzes the issue of admissibility of causing harm to the rapist who perpetrated an encroachment on the sexual freedom of a woman, since, in a case of rape, it is difficult, or even impossible, to predict potential harm (loss of a child, infertility, venereal disease, mental disorder).
Public Danger and Some Legal Positions in Rape Cases Quqlification
Keywords: згвалтування; вбивство жертви; суспільна небезпека; статева свобода; статева недоторканість; необхідна оборона; rape; murder of a victim; public danger; sexual freedom; sexual inviolability; necessary defense